Chinese Self, Australian Other: Chinese as a Foreign Language Teacher Identity Construction in Australian Contexts - Han, Yu; Ji, Xiaoyan (Frontiers in Psychology, 2021)
Research in the field of Chinese as a foreign language (CFL) education has been increasing in the past decades. However, the number of studies on CFL teacher identity is limited. To bridge the gap, this study employed a qualitative method to explore Chinese CFL teachers’ identity formation and reformation in Australian contexts. A Chinese-Australian language program was studied to examine the challenges, struggles and developments of Chinese CFL teachers who came to Australia to pursue professional growth. Five Master’s theses and three interview participants were included to paint a picture of how Chinese CFL teachers interact internally and externally with a new environment. Guided by Mead’s theory of self and other, we found that Chinese CFL teachers’ identity formation and reformation in Australian classrooms are deeply influenced by their self-identification and their integration with others in the community. Cultural connectedness is a key for organizational attitudes in the relationship of self and other. Chinese CFL teachers were found lacking the wholeness of self in Australian contexts, which led to obstacles in teacher identity construction. Insufficient communication between self and other resulted in their positioning crisis.